Acute cholecystitis with Cholecystocolic fistula: a case report and pertinent literature review - Alqunai, Mansur S.; Daif-Allah, Mahmoud Abdul-Kareem; Alhammad, Loai (International Surgery Journal, 2017)
Cholecystocolic fistula (CCF) is a rare late complication of gallstones. The clinical features of CCF are nonspecific and variable. No single test is sufficient to diagnose CCF because of the low sensitivity of the tests or the invasive nature of the procedures, and these tests are not routinely requested for asymptomatic patients. Because CCF is rarely diagnosed preoperatively, patient history, laboratory, and radiological data play an important role in alerting surgeons to the possible existence of a CCF. Treatment involves closing the fistula and performing an open or laparoscopic cholecystectomy.